Long-Lasting Effects of Human Mesenchymal Stem Cell Systemic Administration on Pain-Like Behaviors, Cellular, and Biomolecular Modifications in Neuropathic Mice - Siniscalco, Dario; Giordano, Catia; Galderisi, Umberto; Luongo, Livio; de Novellis, Vito; Rossi, Francesco; Maione, Sabatino (Frontiers in Integrative Neuroscience, 2011)
Background. Neuropathic pain (NP) is an incurable disease caused by a primary lesion in the nervous system. NP is a progressive nervous system disease that results from poorly defined neurophysiological and neurochemical changes. Its treatment is very difficult. Current available therapeutic drugs have a generalized nature, sometime acting only on the temporal pain properties rather than targeting the several mechanisms underlying the generation and propagation of pain. Methods. Using biomolecular and immunohistochemical methods, we investigated the effect of the systemic injection of human mesenchymal stem cells (hMSCs) on neuropathic pain relief. We used the spared nerve injury (SNI) model of neuropathic pain in the mouse. Human MSCs were injected into the tail vein of the mouse. Stem cell injection was performed 4 days after sciatic nerve surgery. Neuropathic mice were monitored every 10 days starting from day 11 until 90 days after surgery. Results. Human MSCs were able to reduce pain-like behaviours, such as mechanical allodynia and thermal hyperalgesia, once injected into the tail vein. An anti-nociceptive effect was detectable from day 11 post surgery (7 days post cell injection). Human MSCs were mainly able to home in the spinal cord and pre-frontal cortex of neuropathic mice. Injected hMSCs reduced the protein levels of the mouse pro-inflammatory interleukin IL-1ß and IL-17 and increased protein levels of the mouse anti-inflammatory interleukin IL-10, and the marker of alternatively activated macrophages CD106 in the spinal cord of SNI mice. Conclusions. As a potential mechanism of action of hMSCs in reducing pain, we suggest that they could exert their beneficial action through a restorative mechanism involving: i) a cell-to-cell contact activation mechanism, through which spinal cord homed hMSCs are responsible for switching pro-inflammatory macrophages to anti-inflammatory macrophages; ii) secretion of a broad spectrum of molecules to communicate with